2015
DOI: 10.1093/cid/civ656
|View full text |Cite
|
Sign up to set email alerts
|

Pretreatment HIV Drug Resistance Increases Regimen Switches in Sub-Saharan Africa

Abstract: Given rising pretreatment HIV drug resistance levels in sub-Saharan Africa, these findings underscore the need for expanded access to second-line ART. VL monitoring can improve the accuracy of failure detection and efficiency of switching practices.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
48
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 48 publications
(54 citation statements)
references
References 35 publications
4
48
2
Order By: Relevance
“…The impact of PDR on virologic outcomes among newly-diagnosed HIV infected children is not well established in resource-limited settings [22,[36][37][38][39]. In theory, PDR could compromise the efficacy of first-line cART regimens, thereby reducing rates of virological suppression and increasing subsequent rates of virological treatment failure.…”
Section: Discussionmentioning
confidence: 99%
“…The impact of PDR on virologic outcomes among newly-diagnosed HIV infected children is not well established in resource-limited settings [22,[36][37][38][39]. In theory, PDR could compromise the efficacy of first-line cART regimens, thereby reducing rates of virological suppression and increasing subsequent rates of virological treatment failure.…”
Section: Discussionmentioning
confidence: 99%
“…Development of drug resistance in chronic HIV infection has serious implications [5,6]. Apart from the resultant limitations in the choice of effective treatment regimens, there are also extra cost implications associated with switches to second or third line therapy and extra demands on laboratory monitoring of patients [7][8][9]. Transmitted or pretreatment HIV drug resistance has significant impact on effectiveness of antiretroviral therapy.…”
Section: Introductionmentioning
confidence: 99%
“…Treatment guidelines in resource-permitted settings advocate the use of HIVDR monitoring both prior to ART initiation and when treatment failure is suspected 1,2 . There is increasing evidence showing that the presence of minority resistance variants open Scientific RepoRtS | (2020) 10:1634 | https://doi.org/10.1038/s41598-020-58544-z www.nature.com/scientificreports www.nature.com/scientificreports/ (MRV) in the HIV quasispecies (i.e., a swarm of highly-related but genotypically different viral variants) may be clinically significant and increase the risk of virological failure, impair immune recovery, lead to accumulation of drug resistance, increase risk of treatment switches and death [3][4][5][6][7][8] . A nationwide study in Mexico focusing on pretreatment drug resistance (PDR) found that lowering the detection threshold for PDR to 5% versus the conventional 20% improved the ability to identify patients with virological failure 6 .…”
mentioning
confidence: 99%